Effect of zinc fertilization on major plant and soil enzymes in southern laterites - Aswathy U A (Department of Soil Science and Agricultural Chemistry , College of Agriculture, 2019)
The study entitled “Effect of zinc fertilization on major plant and soil enzymes in southern laterites” was carried out in the Department of Soil Science and Agricultural Chemistry, College of Agriculture, Vellayani during the period 2017-19. The study was envisaged to assess the effect of various sources and methods of application of zinc on the activities of major plant and soil enzymes, biochemical and microbial parameters in laterite soils using tomato (Solanum lycopersicum var. Anagha) as a test crop. From the soil test database developed by the Department of Soil Science & Agricultural Chemistry under the project RF-Soil Testing Lab, laterite soils in Neyyatinkkara series with Zn deficiency were identified. Soil samples were collected from these locations and analysed for confirming Zn deficiency. Soil with low Zn status (0.506 ppm) was selected for the study. The second part of the experiment was a field study aimed at evaluating the efficacy of different sources of Zn using tomato (var. Anagha) as the test crop. The study was laid out in Randomized Block Design with eight treatments replicated thrice. The treatments were Absolute control (T1), N, P, K as per POP- 75:45:25 kg ha-1 (T2), N, P, K+ Soil application of Zn as ZnSO4- 10 kg ha-1 (T3), N, P, K+ Foliar application of Zn as 0.5 per cent ZnSO4 (T4), N, P, K+ Zn as Zn EDTA-18 kg ha-1 (T5), N, P, K+ Zn solubilizer -5 per cent (T6), N, P, K+ Zn Humate- 44 kg ha-1 (T7), N, P, K+ K solubilizer 5 per cent (T8). From the study, it was observed that the treatment T7 with the application of N, P, K+ Zn Humate (44 kg ha-1) recorded the highest plant growth and yield attributes such as number of branches per plant (8.3), days to first flowering (31.7), fruits per plant (46.7), fruit length (3.5 cm), total fruit yield (35833.36 kg ha-1) (1.29 kg plant -1) and total dry matter production (0.108 kg plant -1). The same treatment reported the highest value for enzymes such as carbonic anhydrase, peroxidase and catalase viz., 910 EU g-1, 48.17 activity min-1 g-1 and 27.06x103 units ml-1 respectively. The results of indole 3- acetic acid (IAA) (217.83 μg g-1) and lycopene analysis (26.11 μg g-1) also revealed that the same treatment T7 recorded the highest values. It was observed that the treatments did not have a significant effect on plant pigments chlorophyll a and b. The results of post harvest soil analysis revealed a marginal increase in available nutrient content compared to initial status. The treatment T7 with the application of N, P, K+ Zn Humate (44 kg ha-1) recorded the highest mean value for electrical conductivity (EC) (0.172 dS m-1), exchangeable Ca (436.67 ppm) and Mg (166 ppm), available B (0.221 ppm), soil respiration rate (177.14 mg CO2 100 g-1 d-1), microbial biomass carbon (186.67 μg g-1) and enzymatic activities (dehydrogenase and β- glucosidase). Similarly, T7 with the application of N, P, K+ Zn Humate (44 kg ha-1) recorded the highest value for available Zn (5.123 ppm) which was on par with treatment T5 (4.860 ppm).The uptake analysis revealed that the nutrient uptake varied significantly with the treatments. The treatment T7 registered the highest plant uptake of N, Mg, Zn and B (87.87, 75.29, 0.187 and 0.57 kg ha-1 respectively). An incubation study was conducted to monitor the pattern of activity of enzymes such as dehydrogenase, peroxidase and carbonic anhydrase and to evaluate their kinetic parameters for a period of three months. The study was carried with five treatments each replicated four times in CRD pattern. The treatments included were Soil alone (T1), Soil + Zn as 0.5 ppm ZnSO4 (T2), Soil + Zn as 1 ppm ZnSO4 (T3), Soil + Zn as 1.5 ppm ZnSO4 (T4) and Soil + Zn as 2 ppm ZnSO4 (T5). It was observed that the activity of enzymes were significantly influenced by the treatments. The enzymes peroxidase and carbonic anhydrase showed an increasing trend in activity while peroxidase registered a decreasing trend. Treatment T4 with the application of Soil + Zn as 1.5 ppm ZnSO4 registered the highest value for peroxidase (11.98 activity min-1 g-1) and carbonic anhydrase activity (385 EU g-1). The enzyme kinetics study revealed that the lowest km value was noticed for peroxidase (0.17 activity min-1 g-1) and dehydrogenase (0.77μg TPF g-1 24 h-1) on the 84th day. The peak value for Vmax was observed on the 28th day for enzyme dehydrogenase (75.23 μg TPF g-1 24 h-1) and peroxidase (59.43x103activity min-1 g-1). The treatment T5 corresponding with the application of Soil + Zn as 2 ppm ZnSO4 registered the lowest value of Km for carbonic anhydrase (0.89 EU g-1) and dehydrogenase (0.77μg TPF g-1 24 h-1), and the highest Vmax values for peroxidase. A significant positive correlation between soil enzyme (dehydrogenase), plant enzymes (peroxidase and catalase) and Zn with correlation coefficients 0.942**, 0.950** and 0.726** respectively was noticed. Similarly, in the case of regression analysis, the plant enzymes (peroxidase and catalase) and soil enzyme dehydrogenase were dependent on zinc with coefficients (0.001*, 0.001* and 0.041* respectively). From the study it was observed that treatment T7 with the application of N, P, K+ Zn Humate (44 kg ha-1) registered the highest values for soil parameters (EC, available nutrients and soil enzymes) and plant parameters viz., growth, yield and uptake. Similarly it was also observed to be the best source for available Zn followed by T5- N, P, K+ Zn as Zn EDTA (18 kg ha-1). The incubation study revealed that for highest activity of peroxidase and carbonic anhydrase, the rate of Zn application is 1.5 ppm. In enzyme kinetics study, the treatment T5 with the application of Soil + Zn as 2 ppm ZnSO4 was found to be superior than all other treatments. Hence it can be concluded from the present study that the most efficient source of Zn was Zn Humate with an ideal rate of 44 kg ha-1 along with the recommended levels of N, P, K nutrients.